Evaluation of Sticky Rice Flour, Jack Fruit Seed Flour and Tapioca Flour as Fillers in Pork Nuggets : 10.5958/2581-6616.2020.00009.2 - Thomas, R.; Singha, S.; Saikia, M.; Kalita, R.; Baruah , Z.; Saharia , N. (Journal of Meat Science, 2021)
Sticky rice flour, jackfruit seed flour and tapioca flour were evaluated as alternate fillers to completely replace the wheat flour in the  formulation for processing pork nuggets. Incorporation of sticky rice flour and jackfruit seed flour at 3.5% level in the formulation  had no significant effect on any of the important physico-chemical, microbiological and sensory parameters of the nuggets. Products  containing sticky rice flour did show even some of the better quality parameters compared to that containing wheat flour. Also, complete  replacement of wheat flour with tapioca flour in the formulation resulted in significant reduction in most of the physico-chemical and  sensorial properties of nuggets. The results indicated that pork nuggets with ‘very good’ consumer acceptability could be processed by  completely replacing wheat flour with sticky rice flour and jackfruit seed flour as fillers and the products thus processed had a storage  life of 21 days at 4±1oC.
Keywords: Sticky rice flour; Jackfruit seed flour; Tapioca flour; Filler; Pork nuggets